Numerical prediction of springback and ductile damage in rubber-pad forming process of aluminum sheet metal. (October 2016) - Belhassen, L.; Koubaa, S.; Wali, M.; Dammak, F.
Abstract: Rubber forming is a sheet metal forming process using flexible punch or die. In this paper, finite element method is introduced to analyze rubber-pad forming process of aluminum sheet metal. An elasto-plastic constitutive model with J 2 yield criterion and mixed non-linear isotropic/kinematic hardening coupled with Lemaitre's ductile damage has been adopted during flexible forming operation. To model rubber material, a Mooney-Rivlin theory is used in the finite element simulation. A stamping of aluminum sheet metal with soft punch is simulated. A fully coupled elasto-plastic damage model is implemented in ABAQUS/Standard software via UMAT subroutine to study the effect of some key process parameters like hardness of rubber, type of rubber on the variation of the thickness, the springback and damage of aluminum sheet metal. Highlights: Simulation of rubber-pad forming process of aluminum sheet metal using Abaqus/UMAT. Elasto-plasticity J 2 yield criterion, mixed hardening coupled with ductile damage. Influence of hardness and type of rubber on springback and damage. The springback angle increases with the initial aluminum blank thickness. The maximum error of numerical results is about 3% compared to literature.